Ultrastructural study of the female gametophyte and the epistase in cabombaceae and nymphaeaceae - Zini, Lucía Melisa (2016)
Fil: Zini, Lucía Melisa. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.